Josephus Flavius' Bedeutung hinsichtlich der Topographie und Geographie der Levante in hellenistisch-römischer Zeit - Andreas Vonach (Protokolle zur Bibel, 2016)
Flavius Josephus’ main works „Jewish War“ and „Jewish Antiquities“ are full of excurses on geography and topography of Palestine including information about economics, climate and society. These notes are mostly very precise and therefore seem to be the product of the author himself, who had broad knowledge of his country. Nevertheless they also contain some pieces of „ideal geography“, especially when they inform about the most important Jewish regions – as for example Galilee or Jerusalem – or the merits of Herod the Great. All in all they are a very important source about the geography of Palestine during Roman period.